The new Oxford handbook of economic geography - Clark, Gordon L.; Feldman, Maryann P.; Gertler, Meric S.; Wójcik, Dariusz; Kaiser, Angelika (Oxford University Press, 2018)
The first fifteen years of the 21st century have thrown into sharp relief the challenges of growth, equity, stability, and sustainability facing the world economy. In addition, they have exposed the inadequacies of mainstream economics in providing answers to these challenges. This volume gathers over 50 leading scholars from around the world to offer a forward-looking perspective of economic geography to understanding the various building blocks, relationships, and trajectories in the world economy. The perspective is at the same time grounded in theory and in the experiences of particular places. Reviewing state-of-the-art of economic geography, setting agendas, and with illustrations and empirical evidence from all over the world, the book should be an essential reference for students, researchers, as well as strategists and policy makers. Building on the success of the first edition, this volume offers a radically revised, updated, and broader approach to economic geography. With the backdrop of the global financial crisis, finance is investigated in chapters on financial stability, financial innovation, global financial networks, the global map of savings and investments, and financialization. Environmental challenges are addressed in chapters on resource economies, vulnerability of regions to climate change, carbon markets, and energy transitions. Distribution and consumption feature alongside more established topics on the firm, innovation, and work. The handbook also captures the theoretical and conceptual innovations of the last fifteen years, including evolutionary economic geography and the global production networks approach. Addressing the dangers of inequality, instability, and environmental crisis head-on, the volume concludes with strategies for growth and new ways of envisioning the spatiality of economy for the future.
Enthält 45 Beiträge
Keywords: Handbuch; Aufsatzsammlung; Wirtschaftsgeografie